External or internal companion exciting the spiral arms in CQ Tau?. Issue 4 (1st August 2022) - Hammond, Iain; Christiaens, Valentin; Price, Daniel J; Ubeira-Gabellini, Maria Giulia; Baird, Jennifer; Calcino, Josh; Benisty, Myriam; Lodato, Giuseppe; Testi, Leonardo; Pinte, Christophe; Toci, Claudia; Fedele, Davide
ABSTRACT: We present new high-contrast images in near-infrared wavelengths (λ c = 1.04, 1.24, 1.62, 2.18, and 3.78 μm) of the young variable star CQ Tau, aiming to constrain the presence of companions in the protoplanetary disc. We reached a Ks -band contrast of 14 mag with SPHERE/IRDIS at separations greater than 0${_{.}^{′′}}$ 4 from the star. Our mass sensitivity curve rules out giant planets above 4 MJup immediately outside the spiral arms at ∼60 au and above 2–3 MJup beyond 100 au to 5σ confidence assuming hot-start models. We do, however, detect four spiral arms, a double-arc and evidence for shadows in scattered light cast by a misaligned inner disc. Our observations may be explained by an unseen close-in companion on an inclined and eccentric orbit. Such a hypothesis would also account for the disc CO cavity and disturbed kinematics.